Women in small and medium enterprises and entrepreneurship in Japan - S. M. Rebrey (Vestnik MGIMO-Universiteta)
The article undertakes a gender analysis of small and medium enterprises and entrepreneurship in Japan to find out whether they affect gender inequality, women and economy; what women empowerment could bring to the development of SME, entrepreneurship and economy in Japan. To answer these questions the author uses gap analysis (gender wage gap, enterprise size wage gap, education wage gap) per industry in dynamics; international comparisons, institutional analysis, trend analysis, case studies, historical analysis and policy analysis. The research finds out that SMEs in Japan maintain higher level of inequality, comparing to large enterprises. Interlocked business relations between SME and large corporations (keiretsu) and employment structure are major and unique factors that exacerbate gender inequality in Japan. Tracing back how labor relations were organized in Japan, the research finds that the exclusion of women from lifetime employment was supposed to suit women’s best interests, however it resulted in subordinate position and economic dependence of women. Women’s entrepreneurship in Japan presents an area of untapped potentials that could effectively tackle a set of socio-economic problems and impact exponentially women empowerment in Japan. Women business in Japan proves to be effective and profitable and, what is more important, it has a “human face” and occupies (among others) vacant niche of social care, both optimizing and humanizing it. Finally, the research concludes that female entrepreneurship requires more attention and support from the government.